2015
DOI: 10.1107/s2052520615008252
|View full text |Cite|
|
Sign up to set email alerts
|

Octahedral tilting in the tungsten bronzes

Abstract: Possibilities for 'simple' octahedral tilting in the hexagonal and tetragonal tungsten bronzes (HTB and TTB) have been examined, making use of group theory as implemented in the computer program ISOTROPY. For HTB, there is one obvious tilting pattern, leading to a structure in space group P6₃/mmc. This differs from the space group P6₃/mcm frequently quoted from X-ray studies – these studies have in effect detected only displacements of the W cations from the centres of the WO6 octahedra. The correct space grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
31
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 37 publications
5
31
0
Order By: Relevance
“…Octahedral tilting in TTBs is otherwise restricted by the connectivity in the xy plane, which prevents tilting around the z axis. Tilts around axes in the xy plane are however possible, and often lead to a √ 2 × √ 2 × 2 supercell relative to the aristotype [10,38], in line with a recent group-theoretical analysis [39]. A √ 2 × √ 2 × 2 supercell was also reported for pure SN with TTB structure [40], although for intermediate SBN compositions, doubling of the c parameter has to our knowledge not been reported.…”
supporting
confidence: 80%
“…Octahedral tilting in TTBs is otherwise restricted by the connectivity in the xy plane, which prevents tilting around the z axis. Tilts around axes in the xy plane are however possible, and often lead to a √ 2 × √ 2 × 2 supercell relative to the aristotype [10,38], in line with a recent group-theoretical analysis [39]. A √ 2 × √ 2 × 2 supercell was also reported for pure SN with TTB structure [40], although for intermediate SBN compositions, doubling of the c parameter has to our knowledge not been reported.…”
supporting
confidence: 80%
“…1, 2 and 3, and supporting information in Campbell et al (2018). There were tilting patterns, particularly those associated with irrep A þ 6 , that were missed in our earlier work (Whittle et al, 2015). For TTB we found structures associated with all of the irreps Z þ 5 , A À 5 and R 1 -see Tables 4 and 5 As explained by Campbell et al (2018), and emphasized by Phillips (2018), our new analysis rests on a linearization of equations, valid for infinitesimal angles of tilt.…”
mentioning
confidence: 57%
“…In a recent paper on the tungsten bronzes (Whittle et al, 2015) we attempted to enumerate the possibilities for tilting of the WO 6 octahedra in the hexagonal and tetragonal tungsten bronzes. There is no reason to doubt the structures we presented there.…”
mentioning
confidence: 99%
“…Careful Rietveld analysis is required to ascertain the exact nature of this structural distortion. Possible octahedral tilt modes in HTBs were first predicted by Whittle et al (2015) with regards to the aristotype structure, space group P6/mmm, a 0 ' 7, c 0 ' 4 Å . Their work suggested that to maintain the corner-linked network of BO 6 octahedra, tilting could only be introduced via the irreducible representations A 3 + and L 2 À , resulting in models with P6 3 /mmc and P6/mmm symmetry and unit cells of a 0 Â 2c 0 and 2a 0 Â 2c 0 , respectively.…”
Section: Structure Determination From Pndmentioning
confidence: 99%